A3_2 There's 24 Hours In A Day - Goodman, Yianis; Griffiths, Benjamin; Duara, Angaraj; Southern, Alexia P. M. (Physics Special Topics, 2016)
One day on Earth is considered to have 24 hours. However, the time period of rotation of Earth on its axis is 23 hours 56 minutes and 4 seconds. This rotation period is gradually slowing down due to the recession of the Moon from Earth. In this paper we determine the time until the rotation period of Earth would be exactly 24 hours and the distance the moon has to recede to. We find that the lunar average distance must increase by 1,284km to 385,684km, then Earth would have a day comprising of 24 hours. This would take place 33.7 million years from now.